Motivation and innovation role of school’s principal in improving teacher professionalism - Nellitawati, Nellitawati (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
The main purpose of this study is to determine the motivation and innovation role of principals in improving the professionalism of teachers at SMK Negeri in Padang City. The design of mixed methods. A total of 261 teachers were included as respondents to answer the distributed questionnaires, and a total of 12 respondents were included in the interview, consisting of principals and expert teachers. The findings indicate that the main role in improving the professionalism of teachers is still at a moderate level. This study also shows that the role of principal motivation and innovation has a significant influence in improving the professionalism of teachers in teaching and learning. Based on qualitative results determined that the role of principal motivation and innovation is an important factor to improve the professionalism of teachers. This study emphasizes that the role of principal motivation and innovation in enlightening teacher professionalism is an absolute factor.